Internalisasi Moderasi Beragama Anak Usia Dini Melalui Film Animasi dengan Pendekatan Living Quran - Khafidhoh, khafidhoh (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
This article attempts to explore the internalization of religious moderation in early childhood through animated films using a living hadith approach. The golden age is a period that is quite important for the formation of a child's character. At this time, children quite easily absorb any information that is around them. One effort to internalize children is through animated films. This research is qualitative research. Primary data comes from episodes of the films Upin Ipin, Nussa Rara, Riko the Series, and Hafiz Hafizah, while secondary data comes from books, articles, and any information related to this research. The data that has been collected is then analyzed using Media Ecology theory, Marshal McLuhan. The data validity technique is carried out using source triangulation techniques, namely by looking at the suitability between the messages conveyed in the animated films Upin Ipin, Nussa Rara, Riko the Series and Hafiz Hafizah with the verses of the Al-Qur'an (living al-Qur'an). The findings of this research are that the episodes from the animated films Upin Ipin, Nussa Rara, Riko the Series, and Hafiz Hafizah are in accordance with the values ​​of moderation in the verses of the Koran. And the internalization of religious moderation values ​​through This animated film has been proven to be able to be understood by young children more easily